À priori uplift pressure model for concrete dam foundations based on piezometric monitoring data. Issue 11 (11th October 2021) - Pereira, Renato; Batista, António Lopes; Neves, Luís Canhoto; Casaca, João Martins
Abstract: The uplift pressures change the stress state of the rock mass foundation in a coupled hydromechanical process and may compromise the dam stability. Consequently, dam safety regulations specify the maximum values of the hydraulic conductivity and uplift pressures that can usually only be fulfilled after the execution of seepage and uplift control measures. The design of waterproofing and drainage systems is still based on an equivalent continuum approach, even though rock mass foundations are discontinuous media. The analysis of the piezometric monitoring data of several Portuguese large concrete dam foundations reveals that uplift pressures are site-specific and may even vary considerably across a given site, which can be critical for the safety assessment. From the data gathered in several dams, a probabilistic model that can be seen as an a priori prediction model for uplift pressures is proposed. Considering the difficulty in classifying the geologic foundation conditions beneath each piezometer in existing dams, it is assumed that the data come from a mixture of two beta distributions, representing foundations with regular and unfavorable geologic conditions. This model is a significant improvement over available approaches and will be instrumental for the assessment of existing dams and the design of new dams.